Factors Influencing Union Participation - Loh, Su Leng (1995)
The study investigated the factors influencing union participation amongst workers of a well established Japanese textile factory in Penang, Malaysia. Data was collected using survey questionnaires. 230 employees were surveyed from a total of 690. 44 valid questionnaires returned by respondents were analyzed. Intrinsic job satisfaction was found to have significant negative relationship with nonadministrative participation (ordinary member), whereas gender (male) was found to have a significant positive relationship with participation in union administration (committee activities).